2016
DOI: 10.1007/s00296-016-3573-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the accuracy of self-reported osteoporosis in the community

Abstract: We examined the agreement between self-reported osteoporosis and bone mineral density (BMD) results through dual-energy x-ray absorptiometry (DXA) using data from a national representative sample taken from the US communities. Six-year data from the continuous National Health and Nutrition Examination Survey 2005-2006, 2007-2008, and 2009-2010 were merged. Participants included adults 50 years of age or older whose data appeared in both questionnaire and medical examination data files. Self-reported osteoporos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…In our study, the prevalence of self-reported osteoporosis was higher for both sexes across all age groups. The measurement error observed in our study is in accordance with previous work that has demonstrated significant disagreement between self-reported and DXA-confirmed osteoporosis [ 22 , 23 ]. Cadarette et al [ 22 ] found that only 62% with DXA-documented osteoporosis reported their results correctly, with 23% of people with osteoporosis reporting osteopenia and 15% reporting normal bone mass.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, the prevalence of self-reported osteoporosis was higher for both sexes across all age groups. The measurement error observed in our study is in accordance with previous work that has demonstrated significant disagreement between self-reported and DXA-confirmed osteoporosis [ 22 , 23 ]. Cadarette et al [ 22 ] found that only 62% with DXA-documented osteoporosis reported their results correctly, with 23% of people with osteoporosis reporting osteopenia and 15% reporting normal bone mass.…”
Section: Discussionsupporting
confidence: 92%
“…Cadarette et al [ 22 ] found that only 62% with DXA-documented osteoporosis reported their results correctly, with 23% of people with osteoporosis reporting osteopenia and 15% reporting normal bone mass. Likewise, Cunningham et al [ 23 ] demonstrated that many people who self-report osteoporosis are osteopenic indicating confusion between the two conditions [ 24 ] or other health conditions like osteoarthritis [ 25 ], or poor communication of a clear diagnosis from their health care provider [ 22 ]. Factors associated with accurate reporting of a DXA-confirmed osteoporosis diagnosis included female sex, race (non-Hispanic White, Mexican–American, and multiracial), having a lower body mass index, poor health, a history of fracture, and osteoporosis treatment [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-reported measures have limitations (see the Limitations section), but HRS data are the best suited to answering our research questions; data sets that include measured BMD (e.g., National Health and Nutrition Examination Survey) are cross-sectional, have fewer relevant variables, and/or have small samples. A recent study found good to very good concordance between self-reported osteoporosis and records of medication being taken for osteoporosis ( Mannion et al, 2020 ); yet, others show self-reported osteoporosis data to be biased against disease ( Cunningham & DeShields, 2016 ; Simpson et al, 2004 ), suggesting our comparison group includes some individuals with osteoporosis who did not report a diagnosis. Thus, our results likely represent lower-bound estimates.…”
Section: Methodsmentioning
confidence: 98%